Assessing the impact of waste picking on musculoskeletal disorders among waste pickers in Mumbai, India: a cross-sectional study. Issue 9 (24th September 2015) - Singh, Shrikant; Chokhandre, Praveen
Abstract : Objective: To assess the prevalence of musculoskeletal disorders (MSDs) as well as the impact of the occupation of waste picking on complaints of MSDs among waste pickers. The study attempts to understand the risk factors for MSDs in various areas of the body. Design: A cross-sectional household survey was conducted using a case-control design. The survey instrument for measuring musculoskeletal symptoms was adopted from a standardised Nordic questionnaire. The impact of the occupation of waste picking on MSDs was analysed using the propensity score matching (PSM) method. Participants: The study population consisted of waste pickers (n=200) who had been working for at least a year and a control group (n=213) selected from among or living close to the same communities. Results: The 12-month prevalence of MSDs was higher among waste pickers (79%) compared to controls (55%) particularly in the lower back (54–36%), knee (48–35%), upper back (40–21%) and shoulder (32–12%). Similar patterns were observed in the 12-month prevalence of MSDs which prevented normal activity inside and outside the home, particularly for the lower back (36–21%), shoulder (21–7%) and upper back (25–12%) for waste pickers and controls. Analysis of the impact of waste picking on complaints of MSDs suggests that the occupation of waste picking raises the risk of MSDs particularly in the shoulder, lower and upper back. Older age and longer duration of work are significant risk factors for MSDs. Conclusions: The findings suggest a relatively higher prevalence of MSDs among waste pickers, particularly in the lower and upper back and shoulder, compared to controls. Preventive measures and treatment to minimise the burden of MSDs among waste pickers are strongly recommended.